Experimental Evidence of Arctic Summer Mesospheric Upwelling and Its Connection to Cold Summer Mesopause. Issue 18 (22nd September 2017) - Laskar, F. I.; Chau, J. L.; St.‐Maurice, J. P.; Stober, G.; Hall, C. M.; Tsutsumi, M.; Höffner, J.; Hoffmann, P.
Abstract: Common volume mesospheric meteor detections from two radar stations separated by about 130 km were used to retrieve horizontal wind fields between 82 and 96 km altitudes at high latitudes, near 69°N. The horizontal wind divergence was estimated from the gradients of the wind fields. This determination is the first of its kind for the mesosphere. Twelve years of nearly continuous data sets reveal systematic summer signatures in the horizontal wind divergence field, namely, a minimum just below the mesopause. There are indications that the horizontal divergence near the mesopause minimum is correlated with the mesopause temperature. Also, the altitude corresponding to the mesospheric divergence minimum tends to increase over the years. We derived the vertical velocity from the horizontal wind divergence at the mesosphere, which shows upward winds peaking near the mesopause. These winds indicate that adiabatic cooling was strongest at the region of the deep temperature minimum seen in the summer mesopause. Common volume mesospheric meteor detections from two radar stations separated by about 130 km were used to retrieve horizontal wind fields between 82 and 96 km altitudes at high latitudes, near 69°N. The horizontal wind divergence was estimated from the gradients of the wind fields. This determination is the first of its kind for the mesosphere. Twelve years of nearly continuous data sets reveal systematic summer signatures in the horizontal wind divergence field, namely, a minimum just below the mesopause. There are indications that the horizontal divergence near the mesopause minimum is correlated with the mesopause temperature. Also, the altitude corresponding to the mesospheric divergence minimum tends to increase over the years. We show that the reversal in the horizontal wind divergence at the mesosphere is consistent with upward winds peaking near the mesopause. These winds indicate that adiabatic cooling was strongest at the region of the deep temperature minimum seen in the summer mesopause. Common volume mesospheric meteor detections from two radar stations separated by about 130 km were used to retrieve horizontal wind fields between 82 and 96 km altitudes at high latitudes, near 69°N. The horizontal wind divergence was estimated from the gradients of the wind fields. This determination is the first of its kind for the mesosphere. Twelve years of nearly continuous data sets reveal systematic summer signatures in the horizontal wind divergence field, namely, a minimum just below the mesopause. There are indications that the horizontal divergence near the mesopause minimum is correlated with the mesopause temperature. Also, the altitude corresponding to the mesospheric divergence minimum tends to increase over the years. We show that the reversal in the horizontal wind divergence at the mesosphere is consistent with upward winds peaking near the mesopause. These winds indicate that adiabatic cooling was strongest at the region of the deep temperature minimum seen in the summer mesopause. Plain Language Summary: The lowest atmospheric temperatures on Earth are found near 90 km altitude (the mesopause) during summer at polar latitudes. This fact is now well documented and is attributed to a predominance of large amplitude gravity waves carrying eastward momentum near 90 km altitude during summer season. Through a Coriolis deflection, the deposition of this momentum causes equatorward winds at high latitudes, an expansion of the air mass, adiabatic cooling, and an accompanying upward motion of the air. In particular, an experimental determination of the upwelling has been found lacking, owing to the very small vertical motions involved. In this paper, we present a new way to determine the mean vertical motion based on the observation of summer‐long‐averaged horizontal wind divergences obtained by meteor radar measurements observing the same field of view from two separate locations. For 12 consecutive years we have found that the horizontal divergence shows a minimum just below the altitude where the temperature reaches its minimum value. We show that this implies upward velocities of the order of 2 to 10 cm/s reaching their peak in that same region, consistent with the notion of strong adiabatic cooling as the source of the low temperatures. Key Points: For the first time, the horizontal wind divergence has been used to characterize the upper part of the polar summer mesosphere The higher the horizontal wind divergence is, the higher the temperature is around the mesopause The horizontal wind divergence field is consistent with upward vertical winds and adiabatic cooling in the mesopause region